Lithium secondary battery
The lithium secondary battery design addresses stability and swelling issues by using a silicon-based negative electrode and a nonaqueous electrolyte with specific organic solvents to form a stable SEI film, achieving improved durability and performance at high temperatures.
Patent Information
- Application Number
- JP2024552045
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Lithium secondary batteries face challenges with high capacity, high output, and long-term life, particularly in automobile applications, due to instability and swelling issues caused by electrolyte deterioration and transition metal ion elution.
A lithium secondary battery design incorporating a silicon-based negative electrode active material and a nonaqueous electrolyte containing a compound represented by chemical formula 1, along with fluoroethylene carbonate, to form a stable SEI film, enhancing durability and performance at high temperatures.
The proposed battery configuration improves the durability of the negative electrode and maintains performance even under high voltage and high temperature conditions, with enhanced high temperature cycling and storage characteristics.
Smart Images

Figure 2025511475000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0124727 filed on September 29, 2022, and all contents disclosed in the documents of said Korean patent application are incorporated by reference into this specification.
[0002] The present invention relates to a lithium secondary battery. [Background technology]
[0003] Recently, the application areas of lithium secondary batteries have expanded rapidly from supplying power to electronic devices such as electrical, electronic, communication, and computer equipment to storing and supplying power to large-area devices such as automobiles and power storage devices. As a result, there is an increasing need for secondary batteries that have high capacity, high output, and high stability.
[0004] In particular, high capacity, high output, and long life characteristics are important for lithium secondary batteries for automotive applications. To increase the capacity of secondary batteries, nickel-rich positive electrode active materials and silicon-based negative electrode active materials, which have high energy density but low stability, can be used.
[0005] However, when a secondary battery having the above conditions is operated, as charging and discharging proceeds, the coating formed on the surface of the positive / negative electrode or the surface structure of the electrode may deteriorate due to side reactions caused by the deterioration of the electrolyte, and transition metal ions may be eluted from the surface of the positive electrode. The eluted transition metal ions are electro-deposited on the negative electrode, reducing the passivation ability of the SEI, causing the problem of deterioration of the negative electrode.
[0006] Such deterioration of the secondary battery tends to be accelerated when the potential of the positive electrode is high or when the battery is exposed to high temperatures.
[0007] In addition, when a lithium secondary battery is used continuously for a long period of time or left at high temperatures, gas is generated and the thickness of the battery increases, a phenomenon known as swelling. It is known that the amount of gas generated at this time depends on the state of the SEI.
[0008] Therefore, in order to solve these problems, research and development is being conducted on a method to reduce the swelling phenomenon of secondary batteries and improve their stability at high temperatures by forming a stable SEI film on the negative electrode. Summary of the Invention [Problem to be solved by the invention]
[0009] As a result of extensive research to solve the above problems, the present invention aims to provide a lithium secondary battery including an organic solvent for a non-aqueous electrolyte capable of forming a stable SEI film by strong reductive decomposition in an anode including a silicon-based anode active material. The lithium secondary battery according to the present invention provides improved performance by improving high-temperature cycle characteristics and high-temperature storage characteristics. [Means for solving the problem]
[0010] In order to achieve the above object, one embodiment of the present invention provides a lithium secondary battery including a positive electrode containing a lithium nickel cobalt manganese oxide as a positive electrode active material, a negative electrode containing a negative electrode active material made of Si, and a non-aqueous electrolyte containing a lithium salt, an organic solvent, and an additive. The non-aqueous electrolyte of one embodiment of the present invention contains a compound represented by the following formula 1 and fluoroethylene carbonate as an organic solvent, and the compound of formula 1 is contained in an amount of more than 15 wt % based on the total weight of the non-aqueous electrolyte.
[0011] [ka] In the above Chemical Formula 1, A is a cyclic phosphite having 2 or 3 carbon atoms, R is an alkylene group having 1 to 5 carbon atoms, and X is a perfluoroalkyl group having 1 to 5 carbon atoms. Effect of the Invention
[0012] The present invention relates to a lithium secondary battery including a positive electrode and a negative electrode that have a high energy density but poor stability, and the non-aqueous organic solvent contains the compound represented by Chemical Formula 1. The compound represented by Chemical Formula 1 can form a polymerized SEI layer along with strong reductive decomposition, particularly when a Si negative electrode is used, thereby improving the durability of the negative electrode even under conditions such as high voltage and high temperature.
[0013] Specifically, when the compound of Formula 1 is used at a low content at the additive level, the compounds of Formula 1 cannot form a polymer with each other, making it difficult to form a dense SEI layer. However, when the compound of Formula 1 is used at a high content at the organic solvent level, as in the lithium secondary battery of the present invention, a dense and uniform SEI layer having a high ratio of monomers derived from the compound of Formula 1 can be formed, improving the durability of the negative electrode. The lithium secondary battery of the present invention, which has improved negative electrode durability, has the effect of not deteriorating in performance even when exposed to high voltage and high temperature for a long time and operated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0015] In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more different features, numbers, steps, components, or combinations thereof.
[0016] In the present specification, in the description of "carbon number a to b", "a" and "b" refer to the number of carbon atoms contained in a specific functional group. That is, the functional group can contain "a" to "b" carbon atoms. For example, "an alkylene group having 1 to 5 carbon atoms" refers to an alkylene group containing 1 to 5 carbon atoms, i.e., -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH3)CH-, -CH(CH3)CH2-, and -CH(CH3)CH2CH2-.
[0017] In addition, in this specification, the term "alkylene group" means a branched or unbranched divalent hydrocarbon group.
[0018] In this specification, any alkyl group or alkylene group may be substituted or unsubstituted.
[0019] In the present specification, the alkyl group and the like may be either substituted or unsubstituted. The term "substituted" means that at least one hydrogen bonded to a carbon atom is substituted with an element other than hydrogen, unless otherwise specified, and means that the alkyl group has 1 to 20 carbon atoms, the alkenyl group has 2 to 20 carbon atoms, the alkynyl group has 2 to 20 carbon atoms, the alkoxy group has 1 to 20 carbon atoms, the cycloalkyl group has 3 to 12 carbon atoms, the cycloalkenyl group has 3 to 12 carbon atoms, the heterocycloalkyl group has 3 to 12 carbon atoms, the heterocycloalkenyl group has 3 to 12 carbon atoms, the aryloxy group has 6 to 12 carbon atoms, a halogen atom, a nitro group, an aryl group has 6 to 20 carbon atoms, a heteroaryl group has 2 to 20 carbon atoms, a haloaryl group has 6 to 20 carbon atoms, and the like.
[0020] The present invention will now be described in more detail.
[0021] The lithium secondary battery of the present invention includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. Here, the lithium secondary battery of the present invention can be manufactured by a conventional method well known in the art. For example, the positive electrode, the negative electrode, and a separator between the positive electrode and the negative electrode are sequentially stacked to form an electrode assembly, and the electrode assembly is inserted into a battery case and a non-aqueous electrolyte is injected to manufacture the lithium secondary battery.
[0022] Specifically, the lithium secondary battery of the present invention can include a positive electrode including a lithium nickel cobalt manganese-based oxide as a positive electrode active material, a negative electrode including a silicon-based active material as a negative electrode active material, and a non-aqueous electrolyte including a lithium salt, an organic solvent, and an additive.
[0023] The non-aqueous electrolyte included in the lithium secondary battery of the present invention may include a compound represented by the following Chemical Formula 1 as an organic solvent.
[0024] [ka]
[0025] In the above Chemical Formula 1, A is a cyclic phosphite having 2 or 3 carbon atoms. In terms of facilitating the ring-opening reaction for forming the SEI layer, A is preferably a cyclic phosphite having 2 carbon atoms.
[0026] In the above chemical formula 1, R is an alkylene group having 1 to 5 carbon atoms, and preferably an alkylene group having 1 to 3 carbon atoms.
[0027] In the above Chemical Formula 1, X is a perfluoroalkyl group having 1 to 5 carbon atoms, and preferably, X is CF3 or CF2CF3.
[0028] Specifically, the compound of Formula 1 may be a compound of Formula 1-1 below.
[0029] [ka]
[0030] In the above chemical formula 1-1, R may be an alkylene group having 1 to 5 carbon atoms, and preferably an alkylene group having 1 to 3 carbon atoms.
[0031] In the above chemical formula 1-1, R1 and R2 can each independently be H or an alkyl group having 1 to 3 carbon atoms.
[0032] More specifically, the compound of Formula 1 may be a compound of Formula 1-2 below.
[0033] [ka]
[0034] The lithium secondary battery of the present invention may contain the compound of Formula 1 in an amount of more than 15 wt %, preferably 20 wt % to 50 wt %, more preferably 30 wt % to 50 wt %, based on the total weight of the non-aqueous electrolyte. When the content of the compound of Formula 1 satisfies the above range, a dense and uniform SEI layer having a high ratio of monomers derived from the compound of Formula 1 can be formed, and the durability of the negative electrode can be improved. The lithium secondary battery of the present invention with improved negative electrode durability has an effect of not deteriorating in performance even when exposed to high voltage and high temperature for a long time and operated.
[0035] The lithium secondary battery of the present invention contains the compound represented by Chemical Formula 1 and fluoroethylene carbonate (FEC) in the non-aqueous electrolyte. The lithium secondary battery of the present invention contains both the compound represented by Chemical Formula 1 and fluoroethylene carbonate as the organic solvent, so that a strong fluoro-based polymeric coating is formed, and a highly durable coating can be formed on the negative electrode. In addition, the phosphite-derived coating has the effect of excellent lithium ion conductivity and low resistance. It is most preferable that the organic solvent contained in the non-aqueous electrolyte of the lithium secondary battery of the present invention is composed of the compound represented by Chemical Formula 1 and fluoroethylene carbonate.
[0036] The lithium secondary battery of the present invention may contain 5% by weight to 80% by weight, preferably 10% by weight to 70% by weight, and more preferably 20% by weight to 50% by weight of the fluoroethylene carbonate (FEC) based on the total weight of the non-aqueous electrolyte. When the content of FEC satisfies the above range, a highly durable coating film can be formed on the negative electrode.
[0037] The non-aqueous electrolyte of the present invention can further contain at least one organic solvent selected from the group consisting of cyclic carbonate organic solvents, linear carbonate organic solvents, linear ester organic solvents, and cyclic ester organic solvents.
[0038] Preferably, the non-aqueous electrolyte of the present invention may further include a linear carbonate organic solvent as an organic solvent in addition to the compound represented by Chemical Formula 1. The linear carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and representative examples thereof include at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically, diethyl carbonate (DEC) may be included.
[0039] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and can easily dissociate the lithium salt in the electrolyte. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate.
[0040] In addition, the organic solvent may further include at least one ester-based organic solvent selected from the group consisting of linear ester-based organic solvents and cyclic ester-based organic solvents in order to produce an electrolyte having high ionic conductivity.
[0041] Specific examples of such linear ester-based organic solvents include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0042] The cyclic ester organic solvent may be at least one organic solvent selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone.
[0043] Meanwhile, the organic solvent may be any organic solvent commonly used in non-aqueous electrolytes without limitation, if necessary, and may further include at least one of an ether-based organic solvent, a glyme-based organic solvent, and a nitrile-based organic solvent.
[0044] The ether solvent may be any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more of these may be used, but is not limited thereto.
[0045] The glyme-based solvent has a higher dielectric constant and lower surface tension than linear carbonate-based organic solvents, and is less reactive with metals. The glyme-based solvent may include, but is not limited to, at least one selected from the group consisting of dimethoxyethane (DME), diethoxyethane, diglyme, tri-glyme, and tetra-glyme (TEGDME).
[0046] The nitrile-based solvent may be at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, but is not limited thereto.
[0047] The lithium salt contained in the non-aqueous electrolyte of the present invention is used as an electrolyte salt in a lithium secondary battery and as a medium for transferring ions. Usually, the lithium salt contains, for example, Li + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , A.I.C. l4 - , AlO2 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N- , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - and SCN - At least one selected from the group consisting of:
[0048] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2). In addition, any lithium salt commonly used in the electrolyte of a lithium secondary battery may be used without limitation.
[0049] The lithium salt can be appropriately changed within a range that is normally usable, but in order to obtain the optimum effect of forming a corrosion prevention coating on the electrode surface, it can be contained in the electrolyte at a concentration of 0.1 M to 5.0 M, preferably 0.5 M to 3.0 M, and more preferably 1.0 M to 2.0 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics during high-temperature storage of the lithium secondary battery is sufficient, and since the viscosity of the non-aqueous electrolyte is appropriate, the electrolyte impregnation can be improved.
[0050] In addition, the nonaqueous electrolyte of the present invention may further contain a known electrolyte additive in the nonaqueous electrolyte as necessary in order to prevent the nonaqueous electrolyte from decomposing in a high-output environment and causing the collapse of the negative electrode, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and effects of suppressing battery expansion at high temperatures.
[0051] Representative examples of such other electrolyte additives include at least one additive for forming an SEI film selected from the group consisting of cyclic carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0052] The cyclic carbonate compound may be vinylene carbonate (VC) or vinyl ethylene carbonate.
[0053] The sultone compound may be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0054] The sulfate-based compound may be ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).
[0055] The phosphate-based compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalate)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-triple perethyl)phosphate, and tris(2,2,2-triple perethyl)phosphite.
[0056] Examples of the borate-based compound include tetraphenylborate, lithium oxalyl difluoroborate (LiODFB), and lithium bis(oxalato)borate (LiB(C2O4)2, LiBOB).
[0057] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0058] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.
[0059] The lithium salt-based compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, and examples of the lithium salt-based compound include lithium difluorophosphate (LiDFP), LiPO2F2, and LiBF4.
[0060] Among these other electrolyte additives, when a combination of vinylene carbonate (VC), 1,3-propane sultone (PS), and 1,3-propene sultone (PRS) is further included, a stronger SEI coating can be formed on the surface of the negative electrode during the initial activation process of the secondary battery, and the generation of gas that may be generated by decomposition of the electrolyte at high temperatures can be suppressed, thereby improving the high-temperature stability of the secondary battery.
[0061] Meanwhile, the other electrolyte additives may be used in combination of two or more kinds, and may be included in an amount of 0.1 wt% to 10 wt%, specifically 0.2 wt% to 8 wt%, and preferably 0.5 wt% to 8 wt%, based on the total weight of the non-aqueous electrolyte. When the content of the other electrolyte additives satisfies the above range, a more excellent improvement effect on ion conductivity and cycle characteristics is exhibited.
[0062] The positive electrode included in the lithium secondary battery of the present invention can be produced by coating a positive electrode current collector with a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, a solvent, and the like.
[0063] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like can be used.
[0064] The positive electrode included in the lithium secondary battery of the present invention may include a lithium nickel cobalt manganese-based oxide having a high nickel content as a positive electrode active material in order to increase the energy density. Specifically, the lithium nickel cobalt manganese-based oxide may have a composition represented by the following Chemical Formula 2.
[0065] [Chemical formula 2] Li a Ni b Co c M 1 d M 2 e O2
[0066] In the above Chemical Formula 2, M 1 can be Mn or a combination of Mn and Al, and is preferably a combination of Mn and Al from the viewpoint of enhancing structural stability.
[0067] M 2 can be one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb.
[0068] The a represents the atomic fraction of lithium in the lithium nickel cobalt manganese oxide and can be 0.90≦a≦1.1, preferably 0.95≦a≦1.08, and more preferably 1.0≦a≦1.08.
[0069] The b indicates the atomic fraction of nickel among the metal elements other than lithium in the lithium nickel cobalt manganese oxide, and may be 0.80≦b<1.0, preferably 0.80≦b≦0.95, and more preferably 0.80≦b≦0.90. When the nickel content satisfies the above range, high capacity characteristics can be achieved.
[0070] The c represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium nickel cobalt manganese oxide, and is 0 <c<0.2、0<c≦0.15、または0.01≦c≦0.10であることができる。
[0071] The d is M among the metal elements other than lithium in the lithium nickel cobalt manganese oxide. 1 indicates the atomic fraction of 0 <d<0.2、0<d≦0.15、または0.01≦d≦0.10であることができる。
[0072] The e is M among the metal elements other than lithium in the lithium nickel cobalt manganese oxide. 2 and may be 0≦e≦0.1, or 0≦e≦0.05.
[0073] The positive electrode active material may be contained in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solid matters other than the solvent in the positive electrode mixture slurry.
[0074] The binder is a component that serves to bind the active material and conductive material and to bind them to the current collector.
[0075] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.
[0076] Usually, the binder can be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids other than the solvent in the positive electrode mixture slurry.
[0077] The conductive material is a component for further improving the conductivity of the positive electrode active material, and can be added in an amount of 1% by weight to 20% by weight based on the total weight of the solid content of the positive electrode mixture slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples thereof include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powders; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0078] Generally, the conductive material can be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of solid matters other than the solvent in the positive electrode mixture slurry.
[0079] The solvent may include an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a preferred viscosity when the positive electrode active material, and optionally, a binder and a conductive material, are included. For example, the solvent may be included so that the concentration of the solids, including the positive electrode active material, and optionally, a binder and a conductive material, is 50% by weight to 95% by weight, preferably 70% by weight to 95% by weight, and more preferably 70% by weight to 90% by weight.
[0080] The negative electrode included in the lithium secondary battery of the present invention can be produced by coating a negative electrode current collector with a negative electrode mixture slurry containing a negative electrode active material, a binder, a conductive material, a solvent, and the like.
[0081] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, those obtained by surface treatment of the surface of copper or stainless steel with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. Also, similar to the positive electrode current collector, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.
[0082] In order to increase the energy density, the negative electrode included in the lithium secondary battery of the present invention can contain a silicon-based active material as the negative electrode active material. Examples of the silicon-based active material include Si, SiO x (0 < x < 2), etc. The negative electrode active material of the present invention preferably does not contain conventional negative electrode active materials such as graphite and is composed of silicon (Si).
[0083] The negative electrode active material can be contained in an amount of 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, more preferably 80% by weight to 98% by weight, based on the total weight of the solid content in the negative electrode mixture slurry.
[0084] The binder is a component that helps bind the conductive material, active material, and current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers thereof, etc.
[0085] Generally, the binder can be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of solid matters other than the solvent in the negative electrode mixture slurry.
[0086] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1% by weight to 20% by weight based on the total weight of the solid content of the negative electrode mixture slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples thereof include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powders; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0087] The conductive material may be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of solid matters other than the solvent in the negative electrode mixture slurry.
[0088] The solvent may include water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a preferred viscosity when the negative electrode active material, and optionally a binder and a conductive material, are included. For example, the solvent may be included so that the concentration of solids including the negative electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, and preferably 70% by weight to 90% by weight.
[0089] The separator that can be included in the lithium secondary battery of the present invention may be a conventional porous polymer film that has been used as a separator, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, which may be used alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, etc., may be used, but is not limited thereto. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used in a single layer or multilayer structure.
[0090] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0091] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely illustrative for the purpose of facilitating understanding of the present invention, and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications can be made within the scope of the present description and technical ideas, and it goes without saying that such changes and modifications fall within the scope of the appended claims.
[0092] Working Example Example 1 (Production of non-aqueous electrolyte) A non-aqueous solvent was prepared by mixing the compound of formula 1-2 and fluoroethylene carbonate (FEC) in a volume ratio of 20:80. LiPF6 was dissolved in the solvent to a concentration of 1.5M, vinylene carbonate (VC) to a concentration of 0.5 wt%, 1,3-propane sultone (PS) to a concentration of 0.5 wt%, and 1,3-propene sultone (PRS) to a concentration of 0.5 wt% to prepare a non-aqueous electrolyte. In the prepared non-aqueous electrolyte, the compound of formula 1-2 was contained in an amount of 16 wt% based on the total weight of the non-aqueous electrolyte, and FEC was contained in an amount of 71 wt% based on the total weight of the non-aqueous electrolyte.
[0093] [ka]
[0094] (manufacturing lithium secondary batteries) Cathode active material (LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 O2): Conductive material (carbon black): Binder (polyvinylidene fluoride) was added to the solvent N-methyl-2-pyrrolidone (NMP) in a weight ratio of 97.5:1.0:1.5 to prepare a positive electrode slurry (solid content 50 wt%). The positive electrode slurry was applied to one side of a positive electrode current collector (aluminum thin film) with a thickness of 12 μm, and dried and roll pressed to prepare a positive electrode.
[0095] Anode active material (Si): conductive material (carbon black): binder (SBR-CMC) was added to a solvent, N-methyl-2-pyrrolidone (NMP), in a weight ratio of 95:1.5:3.5 to prepare anode slurry (solid content 60 wt%). The anode slurry was applied to one side of anode current collector (Cu thin film) with a thickness of 6 μm, and dried and roll pressed to prepare anode.
[0096] A polyolefin-based porous separator coated with inorganic particles Al2O3 was interposed between the prepared positive electrode and negative electrode in a dry room, and the prepared non-aqueous electrolyte was then injected to prepare a secondary battery.
[0097] Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous solvent prepared by mixing the compound of Formula 1-2 and fluoroethylene carbonate (FEC) in a volume ratio of 30:70 was used. In the manufactured non-aqueous electrolyte, the compound of Formula 1-2 was contained in an amount of 25 wt % based on the total weight of the non-aqueous electrolyte, and FEC was contained in an amount of 62 wt % based on the total weight of the non-aqueous electrolyte.
[0098] Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous solvent prepared by mixing the compound of Formula 1-2 and fluoroethylene carbonate (FEC) in a volume ratio of 50:50 was used. In the manufactured non-aqueous electrolyte, the compound of Formula 1-2 was contained in an amount of 42 wt % based on the total weight of the non-aqueous electrolyte, and FEC was contained in an amount of 45 wt % based on the total weight of the non-aqueous electrolyte.
[0099] Comparative Example 1 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous solvent prepared by mixing the compound of Formula 1-2 and fluoroethylene carbonate (FEC) in a volume ratio of 18:82 was used. In the manufactured non-aqueous electrolyte, the compound of Formula 1-2 was contained in an amount of 15 wt % based on the total weight of the non-aqueous electrolyte, and FEC was contained in an amount of 72 wt % based on the total weight of the non-aqueous electrolyte.
[0100] Comparative Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that graphite was used as the negative electrode active material.
[0101] Comparative Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous solvent prepared by mixing the compound of Formula 1-2 and ethylene carbonate (EC) in a volume ratio of 20:80 was used. In the manufactured non-aqueous electrolyte, the compound of Formula 1-2 was contained in an amount of 18 wt % based on the total weight of the non-aqueous electrolyte, and EC was contained in an amount of 66 wt % based on the total weight of the non-aqueous electrolyte.
[0102] Experimental Example 1: Evaluation of high temperature cycle characteristics The cycle characteristics of each of the secondary batteries produced in Examples 1 to 3 and Comparative Examples 1 to 3 were evaluated.
[0103] Specifically, the batteries produced in Examples 1 to 3 and Comparative Examples 1 to 3 were each charged to 4.2 V at a constant current of 0.33 C at 45° C. and discharged to 3.0 V at a constant current of 0.33 C, which constitutes one cycle, and then the capacity retention rate after 250 cycles relative to the initial capacity was measured. The results are shown in Table 1 below.
[0104] [Table 1]
[0105] As shown in Table 1, the secondary batteries of Examples 1 to 3 had higher capacity retention rates and better life characteristics than the secondary batteries of Comparative Examples 1 to 3.
[0106] Experimental Example 2: Evaluation of high-temperature storage characteristics The secondary batteries produced in Examples 1 to 3 and Comparative Examples 1 to 3 were each evaluated for high-temperature storage characteristics.
[0107] Specifically, the secondary batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were each fully charged to 4.2 V, and then stored at 60° C. for 8 weeks.
[0108] Before storage, the capacity of the fully charged secondary battery was measured and set as the initial capacity of the secondary battery.
[0109] After 8 weeks, the capacity retention rate of the secondary battery stored relative to the initial capacity before storage was measured. The percentage ratio of the capacity of the secondary battery after storage relative to the initial capacity of the secondary battery was calculated to derive the capacity retention rate after 8 weeks. The results are shown in Table 2 below.
[0110] [Table 2]
[0111] As shown in Table 2, the secondary batteries of Examples 1 to 3 had higher capacity retention rates after 8 weeks than the secondary batteries of Comparative Examples 1 to 3, and were confirmed to have stable performance at high temperatures.
Claims
1. A positive electrode containing lithium nickel cobalt manganese oxide as a positive electrode active material; a negative electrode including a negative electrode active material made of Si; A lithium secondary battery comprising a non-aqueous electrolyte containing a lithium salt, an organic solvent, and an additive, The organic solvent includes a compound of the following formula 1 and fluoroethylene carbonate: The compound of Chemical Formula 1 is contained in an amount of more than 15 wt % based on the total weight of the non-aqueous electrolyte. 【Chemistry 1】 In the above formula 1, A is a cyclic phosphite having 2 or 3 carbon atoms; R is an alkylene group having 1 to 5 carbon atoms; X is a perfluoroalkyl group having 1 to 5 carbon atoms.
2. 2. The lithium secondary battery of claim 1, wherein the lithium nickel cobalt manganese oxide has a composition represented by the following Chemical Formula 2: [Chemical formula 2] Li a Ni b Co c M 1 d M 2 e O 2 (In the above Chemical Formula 2, M 1 is Mn or a combination of Mn and Al, M 2 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, and 0.8≦a≦1.2, 0.80≦b<1, 0<c<0.2, 0<d<0.2, 0≦e≦0.
1.
3. 2. The lithium secondary battery of claim 1, wherein the organic solvent comprises the compound of Formula 1 and fluoroethylene carbonate.
4. The lithium salt is LiPF 6 The lithium secondary battery according to claim 1 ,
5. 2. The lithium secondary battery of claim 1, wherein R in Formula 1 is an alkylene group having 1 to 3 carbon atoms.
6. The X is CF 3 or CF 2 CF 3 The lithium secondary battery according to claim 1 ,
7. 2. The lithium secondary battery according to claim 1, wherein the compound of Chemical Formula 1 is a compound of the following Chemical Formula 1-1: 【Chemistry 2】 In the above Chemical Formula 1-1, R is an alkylene group having 1 to 5 carbon atoms, R 1 and R 2 are each independently H or an alkyl group having 1 to 3 carbon atoms.
8. 2. The lithium secondary battery according to claim 1, wherein the compound of Formula 1 is a compound of Formula 1-2: 【Chemistry 3】
9. 2. The lithium secondary battery of claim 1, wherein the compound of Formula 1 is contained in an amount of 20% by weight to 50% by weight based on the total weight of the non-aqueous electrolyte.
10. 2. The lithium secondary battery according to claim 1, wherein the fluoroethylene carbonate is contained in an amount of 5% by weight to 80% by weight based on the total weight of the non-aqueous electrolyte.
Citation Information
Patent Citations
Lithium-ion battery and non-aqueous electrolyte therefor
CN108365265A
Nonaqueous electrolyte and nonaqueous electrolyte battery using the same
JP2011108454A
Electrode for secondary battery and lithium secondary battery including the same
JP2019501492A
Electrolyte having a phosphite as an additive or cosolvent, lithium secondary battery having this electrolyte, and method for producing the phosphite
JP2021528806A
Organic electrolytic solution and lithium battery using the same
US20070048622A1